2018
DOI: 10.1101/413245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Histone Demethylase KDM4D Promotes Hepatic Fibrogenesis by Modulating Toll-Like Receptor 4 Signaling Pathway

Abstract: Potential conflict of interest: Nothing to report.Abbreviations: HSC, hepatic stellate cell; H3K9, histone H3 on lysine 9; TLR4, Toll-like receptor 4; α-SMA, α-smooth muscle actin; KMT, lysine methyltransferase; KDM, lysine demethylase; KDM4, lysine (K)-specific demethylase 4; qRT-PCR, quantitative real-time PCR; siRNA, small interfering RNA; FBS, fetal bovine serum; i.p., intraperitoneally; CCl 4 , carbon tetrachloride; TAA, thioacetamide; BDL, bile duct ligation; AAV, adeno-associated virus;shRNA, short-hair… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…In our in vivo experiments, we found that the liver tissue structure was severely damaged after treatment with CCl 4 (Figure 1d), where collagen was excessively accumulated (Figure 2b), and ALT, AST, ALP, γ‐GT, and TBIL had a significant rise in the activity or there was an elevated content of HA, LN, PC‐III, IV‐C, α‐SMA, and TGF‐β1 (Figures 1–2). The above indicators demonstrate that our in vivo animal model of hepatic fibrosis was successfully established (Dong et al, 2019; Liao et al, 2019; Lin et al, 2018). In addition, HSC‐T6 cells were then treated with TGF‐β1, which represented a mature model of hepatic fibrosis in vitro (He et al, 2016; Qin et al, 2018).…”
Section: Discussionmentioning
confidence: 68%
“…In our in vivo experiments, we found that the liver tissue structure was severely damaged after treatment with CCl 4 (Figure 1d), where collagen was excessively accumulated (Figure 2b), and ALT, AST, ALP, γ‐GT, and TBIL had a significant rise in the activity or there was an elevated content of HA, LN, PC‐III, IV‐C, α‐SMA, and TGF‐β1 (Figures 1–2). The above indicators demonstrate that our in vivo animal model of hepatic fibrosis was successfully established (Dong et al, 2019; Liao et al, 2019; Lin et al, 2018). In addition, HSC‐T6 cells were then treated with TGF‐β1, which represented a mature model of hepatic fibrosis in vitro (He et al, 2016; Qin et al, 2018).…”
Section: Discussionmentioning
confidence: 68%
“…Proliferation and activation of hepatic stellate cells (HSC), and balancing extracellular matrix (ECM) synthesis and metabolism have become research hotspots of hepatic fibrosis treatment (4,5). There have been several reports that modification of aberrant histone methylation status may inhibit the proliferation and activation of HSCs to prevent the development of hepatic fibrosis (6,7). Yang et al (6) found that the histone H3K27 methyltransferase inhibitor, DZNep, displays anti-hepatic fibrosis activity through alteration of the aberrant H3K27 methyl group in HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (6) found that the histone H3K27 methyltransferase inhibitor, DZNep, displays anti-hepatic fibrosis activity through alteration of the aberrant H3K27 methyl group in HSCs. Dong et al (7) demonstrated that knockout of lysine demethylase 4D (KDM4D) protein, a demethylase of H3K9 and H3K36, increased methylation levels of H3K9 and H3K36 in HSCs to decrease α-smooth muscle actin (SMA) and Col I expression, thereby inhibiting the proliferation and activation of HSC. The results of these studies indicated that reduction of histone methylation in activated HSCs by corresponding inhibitors or siRNA methods may inhibit HSC proliferation and activation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation